Kulturaspekter i teknisk oversættelse – en ny runde i et gammelt spil - Kastberg, Peter (HERMES - Journal of Language and Communication in Business, 2002)
My point of departure is opposition towards what seems to be a stereotypical notion of technical communication; namely that it is an instance of domain-specific communication devoid of cultural context, a cultural tabula rasa, so to speak. The main focus of this article is to discuss critically this notion and – on the basis of this diskussion – to point to the drawing of a clear line between the technical matter on the one hand and the textualization of technical matter on the other hand.